WINTER RYE BREEDING ON HIGH AND LOW WATER EXTRACT VISCOSITY - A. A. Goncharenko; I. A. Ermakov; A. V. Makarov; T. V. Semenova; V. N. Tochilin; A. V. Osipova; E. N. Lasareva; O. V. Krakhmaleva (Зерновое хозяйство России, 2018)
The results of divergent selection among winter rye varieties ‘Alfa’ and ‘Moskovskaya 12’ according to their water extract viscosity (WEV) have been presented. The efficiency of the selection depended on variety geno type and on direction of the selection.  Selection in a plus-direction was more efficient, than in a minus-direction. The asymmetry of the result revealed in the first cycle of the selection and continued in the further ones. The rye populations with high viscosity had better bread-making characteristics than those ones with low viscosity.  They surpassed the other varieties in a higher nature of grain (on 4,9%), size of grain (on 14,8%), falling number (on 90s), a rate of amylogram (on 328 e.a.), temperature of gelatinization (on 2,5°С). The varieties with low viscosity produced deliquescent bread with a large pored, soft crumb. The reasons of asymmetry and varieties’ response to selection are being discussed.